Kemandirian Belajar Siswa Dalam Pembelajaran Matematika Model Blended Learning Berbasis Self Explaining Learning - Anwariani, Annisa Rizka; Sadieda, Lisanul Uswah; Reny, Riska (Media Pendidikan Matematika, 2026)
This study aims to examine the level of students’ learning independence through the implementation of a blended learning model with a self-explaining learning approach in mathematics instruction. Learning independence is a key aspect in the digital era, requiring students to be more active, autonomous, and responsible in the learning process. Using a qualitative approach with a descriptive design, the research involved 34 students of SMPN 3 Waru, with data collected through a learning independence questionnaire, in-depth interviews, and observation. The findings revealed that most students were in the medium category (average score of 68.54%), with the highest percentage in the self-confidence aspect at 72.4% (high category) and the lowest in the discipline aspect at 63.6% (low category). These results indicate that the implementation of blended learning based on self-explaining learning can strengthen students’ independence, especially in terms of personal autonomy, although additional strategies are still needed to enhance responsibility and initiative, and overall, the study provides positive implications for the development of mathematics learning strategies that emphasize fostering student independence.